Magical Medicine?: Japanese Buddhist Medical Knowledge and Ritual Instruction for Healing the Physical Body - Triplett, Katja (Japanese religions, 2012)
This article surveys textual sources that pertain to ‘medicine’ as a set of ideas produced and maintained as a social and cultural system of knowledge in early and medieval Japanese Buddhism. Terminological problems faced in working on this material such as ‘religious’ or ‘magical healing’ as opposed to ‘secular, scientifi c and evidence-based medicine,’ are assessed. Th e sources under investigation in this article treat both ritual and medical knowledge in a combined way: Japanese medical works that are usually thought to be secular such as the court physician’s Ishinpōactually quote numerous Buddhist sources. Buddhist monastics and powerful lay patrons actively engaged in obtaining medico-religious knowledge as shown in the case of the materia medica compiled by the Shingon monk Ken’i in the 12th century. In addition to aristocratic members of the elite, semi-ordained “miracle working” healers seem to have had a signifi cant impact on the production of knowledge as well. Th e article concludes with a reconsideration of basic categories derived from the “Western” intellectual tradition and suggests focusing more on the syncretistic and pluralistic nature of the Japanese healing system as encountered in the primary sources.